Design and Evaluation of an Illusion of Explanatory Depth Scale and Its Relationship to Certain Variables - Hawil, Rasool Abdul Ali; Hatami, Jawad; Al-Daghestani, Sanaa Isa (Journal of Cultural Analysis and Social Change, 2025)
The Illusion of Explanatory Depth (IOED) is a cognitive bias that causes individuals to overestimate their knowledge about various topics based on incomplete or misleading information. It represents a behavioral phenomenon prevalent in societies, occurring when individuals believe they understand a concept more deeply than others actually do. The IOED is significant because it exposes the ignorance underlying many societal behaviors and false claims, often resulting in social divisions when individuals perceive themselves as experts in specific fields. This study aimed to measure the level of IOED among a sample of government employees and examine differences based on gender (male–female), educational attainment (PhD, Master’s, Institute, Bachelor’s, Secondary), and age (20–59 years). The sample consisted of 400 employees, selected using a stratified random sampling method with equal distribution. Statistical analysis revealed that government employees exhibited a high level of IOED, with a mean score of 6.50, indicating that they tend to exaggerate their knowledge in front of others. No statistically significant differences in IOED were found across gender, educational attainment, or age.